From Ancient DNA to Modern Livestock: Paleogenomics - Naveen Kumar Sheoran (International Journal of Genetic Modifications and Recombinations, 2023)
Paleogenomics, an interdisciplinary blend of paleontology and genomics, has revolutionized our understanding of ancient DNA and its applications across various fields. In Animal Genetics and Breeding, this field has emerged as a pivotal tool providing invaluable insights into the historical genetics of domesticated animals. By reconstructing and analyzing the genomes of long-extinct organisms, paleogenomics sheds light on genetic diversity, evolutionary dynamics, and adaptations of ancient species. Paleogenomics significantly impacts animal breeding by uncovering the genetic heritage of livestock animals like cattle, pigs, sheep, and chickens. The ancient DNA study also contributes to understanding genetic adaptations and disease resistance. By comparing ancient and modern genomes, researchers discern historical genetic changes that conferred resilience and adaptation to specific environments. The knowledge of past genetic variations helps guide selective breeding efforts in present animal populations. It enables the rediscovery of lost genetic variations due to human-driven selection and bottlenecks, helping create breeding and conservation plans that prioritize diversity. Although challenges exist in working with fragmented and degraded ancient DNA, advancements in sequencing technologies and extraction methods provide hope for overcoming these obstacles. Furthermore, the reconstruction of genomes from extinct species holds promise for conservation efforts and may restore genetic diversity. As paleogenomics advances, the potential to refine techniques and extract even older DNA samples promises a deeper understanding of genetic variants and the evolution of the human genome over time.
Keywords: Breeding; DNA; Genetics; Livestock; Paleogenomics